Resilience measurement scale in family caregivers of children with cancer: Multidimensional item response theory modeling - Jiménez, Said; Moral de la Rubia, José; Varela-Garay, Rosa María; Merino-Soto, Cesar; Toledano-Toledano, Filiberto (Frontiers in Psychiatry, 2023)
Currently, information about the psychometric properties of the Resilience Measurement Scale (RESI-M) in family caregivers of children with cancer according to item response theory (IRT) is not available; this information could complement and confirm the findings available from classical test theory (CTT). The objective of this study was to test the five-factor structure of the RESI-M using a full-information confirmatory multidimensional IRT graded response model and to estimate the multidimensional item-level parameters of discrimination (MDISC) and difficulty (MDIFF) from the RESI-M scale to investigate its construct validity and level of measurement error. An observational study was carried out, which included a sample of 633 primary caregivers of children with cancer, who were recruited through non-probabilistic sampling. The caregivers responded to a battery of tests that included a sociodemographic variables questionnaire, the RESI-M, and measures of depression, quality of life, anxiety, and caregiver burden to explore convergent and divergent validity. The main findings confirmed a five-factor structure of the RESI-M scale, with RMSEA=0.078 (95% CI: 0.075, 0.080), TLI = 0.90, and CFI = 0.91. The estimation of the MDISC and MDIFF parameters indicated different values for each item, showing that all the items contribute differentially to the measurement of the dimensions of resilience. We conclude that regardless of the measurement approach (IRT or CTT), the five-factor model of the RESI-M is valid at the theoretical, empirical, and methodological levels.